Prioritization to protect springs for public urban water supplies, based on multi-criteria evaluation and GIS (State of Mexico, Mexico). (June 2019) - López, Sonia; Expósito, José L.; Esteller, María V.; Gómez, Miguel A.; Franco, Roberto; Morales, Guillermo P.
Abstract: The problematic that commonly arises when protecting springs that supply water for human consumption requires a methodological process to prioritize springs that are used for this purpose according to their greatest need for protection from contamination and exploitation processes. To this end, the stages included in the present study were: a) regionalization of the study area (State of Mexico, Mexico) considering physical variables, which included precipitation, hydrogeological functioning, and geoforms; b) selection of the springs used for human supply that have the greatest exploitation flows, as registered in the Public Water Rights Record; and c) prioritization of springs to be protected based on a multi-criteria evaluation (MCE), considering criteria such as exploitation flow, land use, population to be supplied, conservation of spring water collection systems, existence of alternative supply sources, and marginalization index of nearby populations. Regionalization enabled identifying regions that were homogeneous in terms of the characteristics of the springs and their physical environment. Six of those regions with the largest territorial areas were selected, where 88% of the springs used for human consumption were located. Within each selected region, the springs that were representative of exploitation flow were identified, and a total of 23 were included. Lastly, MCE permit to identify six springs (one in each region) that were priorities for protection. The prioritization of the springs to be protected in each of the six regions selected will facilitate the future application of protection methods based on the physical characteristics of the springs and their physical and socioeconomic environments. Considering also the characteristics of groundwater flow in the feeding areas of the springs. Highlights: The springs of the study area were prioritized for their protection. Regionalization allowed to identify areas with homogeneous physical characteristics. The physical and social characteristics were considered for prioritization. The multi-criteria evaluation and GIS allowed to identify priority springs.